The relationship between staff skill mix, costs and outcomes in intermediate care services - Martin Graham P; Nancarrow Susan; Kaambwa Billingsley; Dixon Simon; Bryan Stirling (BMC, 2010)
Abstract Background The purpose of this study was to assess the relationship between skill mix, patient outcomes, length of stay and service costs in older peoples' intermediate care services in England. Methods We undertook multivariate analysis of data collected as part of the National Evaluation of Intermediate Care Services. Data were analysed on between 337 and 403 older people admitted to 14 different intermediate care teams. Independent variables were the numbers of different types of staff within a team and the ratio of support staff to professionally qualified staff within teams. Outcome measures include the Barthel index, EQ-5D, length of service provision and costs of care. Results Increased skill mix (raising the number of different types of staff by one) is associated with a 17% reduction in service costs (p = 0.011). There is weak evidence (p = 0.090) that a higher ratio of support staff to qualified staff leads to greater improvements in EQ-5D scores of patients. Conclusions This study provides limited evidence on the relationship between multidisciplinary skill mix and outcomes in intermediate care services.